Book Reviews - Redactie KITLV (NWIG, 2010)
Constructing Early Modern Empires: Proprietary Ventures in the Atlantic World, 1500-1750, edited by L.H. Roper & B. Van Ruymbeke (Elizabeth Mancke)

Havana and the Atlantic in the Sixteenth Century, by Alejandro de la Fuente with the collaboration of C